Ghana : Report on the Observance of Standards and Codes (ROSC), Corporate Governance Country Assessment - World Bank (Washington, DC, 2012)
This report assesses Ghana's corporate governance policy framework, enforcement and compliance practices. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Ghana. Ghana is a promising capital market with remarkable recent performance, significant momentum and will for improvement. Continuing challenges are presented however, by its weak institutional base and capacity, as well as by persistent gaps in enforcement. The report identifies several key next steps that focus on implementation, including: 1. A concentrated effort to raise awareness of corporate governance, transparency and accountability. The effort should include director training, possibly with Securities and Exchange Commission (SEC) certification requirements. 2. An overhaul of the institutional framework and capacity, including training, resources, and effectiveness. Particular focus should be directed at promoting the new specialized commercial court, and private arbitration; developing a central depository system for equities; creating an effective companies registry; and improving enforcement of accounting and auditing. 3. Continued legislative review and modernization. 4. An improvement of SEC resources and training would enable it to focus on rule-making and enforcement of disclosure quality, related party transactions, insider trading, ownership disclosure (especially by directors and insiders), management of conflicts of interest among market operators, and shareholder redress. Improved electronic market surveillance by the Ghana Stock Exchange will assist with this ambitious agenda. These measures will help develop Ghana's capital markets, attract investors, and promote best practice of investor protection.